Empowering older adults: evaluating the impact of a smartphone education app on independent living - Woo, Ye-Shin; Shin, Ga-in; Park, Hae Yean (Frontiers in Public Health, 2024)
Purpose As science and technology advance, older people’s ability to use smart devices in their daily living is becoming more demanding. This study addresses the increasing use of smartphones by the older adults, who often struggle with technology due to lack of competence. We developed an educational app tailored for older adults users and compare its effectiveness with existing educational videos. Methods An app was created based on the learning characteristics of the older adults, using the ADDIE model, and compared with traditional video education. It involved six participants aged 65 or older, and convenience sampling method was used, evaluating the app and video through usability assessments and eye tracking. Quantitative and qualitative analyzes were conducted with focus groups under the researcher’s control. Results The app received higher usability scores than the video in content, motivation, and interaction. Eye tracking showed users paid more consistent attention to the app. Conclusion The smartphone app facilitates learning for the older adults without the constraints of time and place, improving their quality of life and technology skills. Eye tracking can be instrumental in future app development for this demographic.